Tbx1 represses Mef2c gene expression and is correlated with histone 3 deacetylation of the anterior heart field enhancer - Luna Simona Pane; Filomena Gabriella Fulcoli; Andrea Cirino; Alessandra Altomonte; Rosa Ferrentino; Marchesa Bilio; Antonio Baldini (The Company of Biologists, 2018)
The TBX1 gene is haploinsufficient in 22q11.2 deletion syndrome (22q11.2DS), and genetic evidence from human patients and mouse models points to a major role of this gene in the pathogenesis of this syndrome. Tbx1 can activate and repress transcription, and previous work has shown that one of its functions is to negatively modulate cardiomyocyte differentiation. Tbx1 occupies the anterior heart field (AHF) enhancer of the Mef2c gene, which encodes a key cardiac differentiation transcription factor. Here, we show that increased dosage of Tbx1 correlates with downregulation of Mef2c expression and reduced acetylation of its AHF enhancer in cultured mouse myoblasts. Consistently, 22q11.2DS-derived and in vitro-differentiated human induced pluripotent stem cells (hiPSCs) expressed higher levels of MEF2C and showed increased AHF acetylation, compared with hiPSCs from a healthy donor. Most importantly, we show that in mouse embryos, loss of Tbx1 enhances the expression of the Mef2c-AHF-Cre transgene in a specific region of the splanchnic mesoderm, and in a dosage-dependent manner, providing an in vivo correlate of our cell culture data. These results indicate that Tbx1 regulates the Mef2c AHF enhancer by inducing histone deacetylation.